Evaluating apheresis platelets at reduced dose as a contingency measure for extreme shortages. Issue 1 (10th November 2021) - Smethurst, Peter A.; McAndrew, Margaret; Proffitt, Susan; Procter, Simon; Davies, Jane; New, Helen V.; Stanworth, Simon J.; Doughty, Heidi; Cardigan, Rebecca
Abstract: Background: The COVID19 pandemic highlights the need for contingency planning in the event of blood shortages. To increase platelet supply, we assessed the operational impact and effect on platelet quality of splitting units prior to storage. Study design and methods: Using production figures, we modeled the impact on unit numbers, platelet counts, and volumes of splitting only apheresis double donations into three units (yielding ⅔ doses), or all standard dose units in half. To assess quality, eight pools of three ABO/Rh‐matched apheresis (Trima Accel) double donations in plasma were split to ⅔ and ½ volumes in both Terumo and Fresenius storage bags. These were irradiated and subject to maximal permitted periods of nonagitation (3 × 8 h) before comparing platelet quality markers (including pH, CD62P expression) to Day 9 of storage. Results: Splitting all double donations into three predicted inventory expansion of 23% overall whereas halving all standard dose units clearly doubles stock. In our study, ⅔ and ½ doses contained 153 ± 15 × 10 9 (~138 ml) and 113 ± 11 × 10 9 (~102 ml) platelets respectively. Following storage, higher pH was observed in ⅔ than in ½ doses and in Terumo compared to Fresenius bags. The higher pH was reflected in better quality markers, including lower CD62P expression. Despite the differences, on Day 8 (of pH monitoring at expiry) all ⅔ doses and most ½ doses were ≥pH 6.4. Conclusion: A strategy to split apheresis platelets in plasma to lower doses is feasible, maintains acceptable platelet quality, and should be considered by blood services in response to extreme shortages.